High-Order Low Dissipation Conforming Finite-Element Discretization of the Maxwell Equations (Communications in Computational Physics, 2012)
In this paper, we study high order discretization methods for solving theMaxwell equations on hybrid triangle-quad meshes. We have developed high orderfinite edge element methods coupled with different high order time schemes and wecompare results and efficiency for several schemes. We introduce in particular a classof simple high order low dissipation time schemes based on a modified Taylor expansion.